The Influence of Product Quality, Promotion, and Location on Consumer Purchase Decisions at Mie Kering Dian Singkawang - Siti Dhea Assyari; Muhammad Ebuziyya Alif Ramadhan (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the influence of product quality, promotion, and location on consumer purchase decisions at Rumah Makan Mie Kering Dian Singkawang. This research employs a quantitative approach with an associative research design. The research population consists of all consumers of Mie Kering Dian Singkawang, with a sample size of 162 respondents determined through purposive sampling techniques. Data were collected using Likert-scale questionnaires supported by interviews and observations. Data analysis was conducted using multiple linear regression with the assistance of SPSS software, preceded by validity testing, reliability testing, and classical assumption tests. The results indicate that product quality, promotion, and location partially have a positive and significant effect on consumer purchase decisions. The regression coefficient for product quality is 0.330, promotion is 0.146, and location is 0.272. Simultaneously, the three variables significantly influence purchase decisions with an F-statistic value of 81.353 and a significance level of < 0.05. The coefficient of determination value of 0.515 indicates that 51.5% of the variation in purchase decisions can be explained by product quality, promotion, and location. This study concludes that these three variables play an important role in shaping the purchase decisions of consumers at Mie Kering Dian Singkawang.